Relaksasi Benson dan Penurunan Kecemasan Pasien Gagal Ginjal yang Sedang Menjalani Hemodialisa - Eltafianti, A Aulia; Widyastuti, Widyastuti; Ridfah, Ahmad (Program Studi Psikologi Universitas Pendidikan Indonesia, 2022)
Abstract This research aimed to determine the effect of Benson relaxation to reduce the level of anxiety on chronic renal failure patients undergoing hemodialysis. The total number of subjects are 5 patients with chronic renal failure who had comorbid hypertension who undergoing hemodialysis and scored high on anxiety. The instrument used in this research was an adaptation of the State-Trait State Anxiety Inventory short revision version scale with state scale reliability value of 0,924 and trait scale of 0,936. The data were analyzed using paired sample t-test. This research is quasy experimental using experimental design one group pretest-posttest design. The result showed that there is a significant effect of Benson relaxation on anxiety of chronic renal failure patients undergoing hemodialysi. The mean of pretest score was 23,4 and posttest score was 9,6. The implication of this research is that applying Benson relaxation before hemodialysis can help to reduce the degree of anxiety on chronic renal failure patients undertake hemodialysis.Keywords: anxiety, benson relaxation, chronic renal failure, hemodialysisAbstrakPenelitian ini bertujuan untuk mengetahui pengaruh relaksasi Benson terhadap kecemasan pasien gagal ginjal yang sedang menjalani hemodialisa. Responden penelitian yaitu sebanyak 5 pasien gagal ginjal yang memiliki penyakit komorbid hipertensi yang menjalani hemodialisa dan memiliki skor kecemasan tinggi. Alat ukur yang digunakan merupakan adaptasi skala State-Trait Anxiety Inventory short revision version dengan nilai reliabilitas skala state sebesar 0,924 dan skala trait sebesar 0,936. Penelitian ini menggunakan rancangan one group pretest-posttest design. Metode analisis data yang digunakan adalah menggunakan paired samples t-test. Hasil analisis data menunjukkan bahwa terdapat pengaruh relaksasi Benson terhadap penurunan kecemasan pasien gagal ginjal yang sedang menjalani hemodialisa. Mean pretest sebesar 23,4 dan mean posttest sebesar 9,6. Implikasi penelitian ini adalah relaksasi Benson yang dilakukan sebelum memulai hemodialisa dapat menurunkan kecemasan pasien gagal ginjal yang menjalani hemodialisa.Kata kunci: gagal ginjal, hemodialisis, kecemasan, relaksasi benson